RETHINGKING MADRASAH EDUCATION OF PRESPECTIVES CLASS MIDDLE - Ruwiah Abdullah Buhungo; Syafrin Ngiode (LP2M IAIN Sultan Amai Gorontalo, 2021)
This research employed qualitative research with a case study approach. A case study is a series of scientific activities carried out intensively, in detail, and in-depth about a program, event, and activity, either at the individual level, or a group of people, institutions, or organizations to gain in- depth knowledge about the event. Likewise, this study explores the role of madrasah education in the perspective of the Muslim middle class in Gorontalo Town, the expectations of the Muslim middle class towards madrasah education in Gorontalo Town, and the contribution of the Muslim middle class to education. This research was conducted at three madrasas, namely at Madrasah Ibtidaiyah Muhammadiyah Unggulan, MTs Negeri Gorontalo, and Madrasah Aliyah Negeri 1 Gorontalo. In this study, the researcher is the main instrument in collecting data. In addition, this study also used interview guidelines, observation, and documentation as supporting tools. Next, data were analyzed using data analysis techniques developed by Miles & Huberman as data collection, data reduction, data display, and conclusion. The result of this study showed that the role of madrasah education in the perspective of the Muslim middle-class community in Gorontalo Town is very positive to include their children in MIM Unggulan Gorontalo and MAN 1 Gorontalo with the perception of the two madrasas as ideal educational institutions in fostering and guide students in both intellectual and spiritual aspects. Likewise, the interest of the Muslim middle class in rural and urban areas is completely high. It is threatened by significant growth in the number of students in both madrasas. In addition, the two madrasas have shown achievement and quality as well as performance both academically and non-academically. The profile of the Muslim middle class of Gorontalo town in perceiving madrasah education has its own advantages like to access classical Islamic repertoire learning resources, such as; the history of Islamic culture, Arabic, Fiqhi/Usul Fiqhi, moral creed, and other factors provide strengthening values attached to the character of students as inherent elements integrated with their personality and behavior of students. All of the scientific treasures at the school provide a strengthening value attached to the character of students as inherent elements integrateding in their personality and behavior of students. The existence of a source of value intrinsic in the appreciation and practice of students in their daily lives is one of the crucial elements needed by the community. Last, Three aspects of desire and contribution of the Muslim middle class to Madrasah education in Gorontalo town, namely Moral, Scientific, and Future.